Os efeitos do gênero e do histórico de Informantes na confiança seletiva de crianças - Messias, Ana Carolina (Universidade Federal de São Carlos, 2019)
Although children use other people’s testimony to learn, recent evidence suggests they do it in a critical manner, trusting their informants selectively. The present study investigated which criterion was privileged by children when deciding whom to trust in novel learning situations – how reliable the informant has been in the past (i.e., his reliability record) or his/her gender. Sixty-three children participated in the study – 32 boys and 31 girls, and they were distributed into two age groups: 3- (M = 3 yrs and 5 mos; SD = 4,3 mos) and 4-year-olds (M = 4 yrs and 5 mos; SD = 5,3 mos). Their vocabulary was assessed by the Peabody Picture Vocabulary Test (PPVT; Brazilian version) and a selective trust task, used in a previous study conducted with U.S. children, was administered. The task was divided into a familiarization phase, and a test phase. During the familiarization phase, children were presented with scenes involving two actors (i.e., informants) labeling familiar objects (i.e., a lamp, a bowl, a coat, a dog). One of these informants was always male and the other female. Participants were distributed into four different conditions. In the first condition (C1), the female informant always labeled the objects correctly, but the male informant labeled incorrectly on every trial. In the second condition (C2), the female informant provided inaccurate labels for all familiar objects, whereas the male informant labeled them accurately every time. In a third condition (C3), both informants provided correct names for the objects. Finally, in the fourth condition (C4), both informants labeled the four objects inaccurately. During the test phase, novel objects were presented and each informant was asked to label them (e.g., one names it “tuma” and the other says it is a “danu”). Results were consistent with prior findings from international studies and they suggest that children tend to prefer the more reliable informant (75% in C1 e 68,7% in C2), regardless of gender. Additionally, when the informants have both proven to be reliable, children preferred the same gender informant (53,3% in C3 e 68,75% in C4). More broadly, these results can add to the existing data from other countries that shows that even young children (3-year-olds) discriminate good and bad informants and select the more reliable when learning something new. More specifically contrary to what many believe, children do not believe everything they hear. At the same time, the present work suggests that selective trust judgments can be influenced by different traits of informants, including gender.
Effects of gender and informants previous history on children's selective trust
Keywords: Confiança seletiva; Gênero; Crianças pré-escolares; Selective trust; Gender; Preschoolers; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO